2017
DOI: 10.1055/s-0043-103017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mangifera indica (Careless) on Microcirculation and Glucose Metabolism in Healthy Volunteers

Abstract: A commercial fruit powder (Careless) showed beneficial acute effects on microcirculation in a randomized, double-blind, crossover pilot study. Here, long-term effects on microcirculation and glucose metabolism were investigated in a double-blind, randomized, placebo-controlled, 3-arm parallel-design study in healthy individuals. A daily dose of 100 mg or 300 mg of the fruit powder was compared to placebo after supplementation for 4 weeks. Microcirculation and endothelial function were assessed by the Oxygen-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Finally, the number of subjects enrolled was comparable to that reported in other studies evaluating the role of cocoa, chocolate and mango in the modulation of endothelial function through PAT technology. [23][24][25][26] Results…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the number of subjects enrolled was comparable to that reported in other studies evaluating the role of cocoa, chocolate and mango in the modulation of endothelial function through PAT technology. [23][24][25][26] Results…”
Section: Discussionmentioning
confidence: 99%
“…In a human pilot study, a powder supplement containing 100% Mangifera indica L. fruit improved microcirculation by potentiating the reactive hyperemia response, an effect which was attributed to the increase in eNOS expression, as observed in endothelial cells in vitro [200]. Another study showed that the same extract was able to improve reactive hyperemia evoked in the postprandial state after a high glucose intake, a factor known to impair the endothelium [201]. To our knowledge, no adverse effects related to Mangifera indica L. intake have been reported.…”
Section: Mangifera Indica Lmentioning
confidence: 93%
“…Buchwald-Werner et al [43] conducted a study investigating the long-term consumption of a commercial powdered M. indica product (Careless™) on microcirculation and glucose metabolism. The researchers deemed these findings promising, indicating a modest beneficial effect of M. indica fruit preparation on microcirculation, endothelial function, and glucose metabolism by the end of the study.…”
Section: Indica and Health Effects: Results From Clinical Trialsmentioning
confidence: 99%